Against dogmatism : dwelling in faith and doubt - Yadlapati, Madhuri M. (University of Illinois Press, 2013)
Defending the rich tapestry of faith and doubt against polarisation, 'Against Dogmatism' reveals a spiritual middle way, an approach native to the long-standing traditions in which faith and doubt are interwoven in constructive and dynamic ways.